A New Analytical Method for Direct Measurement of Particulate and Dissolved B-vitamins and Their Congeners in Seawater - Suffridge, Christopher; Cutter, Lynda; Sañudo-Wilhelmy, Sergio A. (Frontiers in Marine Science, 2017)
We have developed a new method to directly measure the concentration of the particulate and dissolved pools of B-vitamins in seawater. B-vitamins are coenzymes required for life, yet many organisms cannot synthesize these compounds de novo and must scavenge them from the environment. It has been shown that B-vitamins can control the marine microbial community’s structure and activity; however, the actual B-vitamin requirements/quotas for marine microbes are not well studied due to the lack of analytical protocols. This method will enable the study of B-vitamin cellular quotas as well as their environmental cycling. With this method, we can also simultaneously determine the biochemical congeners of vitamins B1 and B12, as well as vitamins B2, B6, B7, and the amino acid methionine in both the particulate and dissolved pool, using liquid chromatography-mass spectrometry after a chemical extraction (particulate) or resin preconcentration (dissolved). Particulate and dissolved B-vitamin concentrations were simultaneously determined from a microbial community in the Atlantic Ocean. Particulate B-vitamin concentrations in the Atlantic ranged from 0.01 pM (cyano-B12) to 46.4 pM (thiamin monophosphate, a B1 congener) while dissolved B-vitamin concentrations ranged from 0.07 pM (adenosyl-B12) to 679.4 pM (B7). The application of this technique in different marine systems has the potential to shed new light on previously unknown biochemical processes occurring within the oceanic microbial community, and the resulting roles B-vitamins play in regulating global biogeochemical cycles.